Risk sharing and commuting among US federal states - Falko Jüßen (Institute for the Study of Labor (IZA), 2008)
Financial markets provide imperfect insurance of labor income risk. However, workers can partly insure against labor market risk by commuting to adjacent regions. Since commuters own wage claims to output produced in adjacent regions, the business cycle in the neighborhood becomes a relevant risk factor at the regional level. In our empirical analysis for US states, we show this effect to be important. State-specific consumption comoves with business cycle shocks that hit adjacent states, in particular if a state is integrated by commuter flows. This labor market perspective on regional risk sharing complements previous studies that investigated risk sharing through financial markets.
Keywords: E21; 330; Risk sharing; consumption smoothing; commuting; labor market risk; Pendelverkehr; Einkommen; Risiko; Regionaler Konjunkturzyklus; Gesamtwirtschaftlicher Konsum; Teilstaat; Regionaler Arbeitsmarkt; USA